The Layered Syntactic Structure of the Complementizer System: Functional Heads and Multiple Movements in the Early Left-Periphery. A Corpus Study on Italian - Moscati, Vincenzo; Rizzi, Luigi (Frontiers in Psychology, 2021)
In this paper we document the developmental trajectory of the complementizer system (CP-system) in Italian by looking at the earliest spontaneous production of eleven young children, whose transcriptions are available on CHILDES (MacWhinney 2000). We conducted a novel corpus analysis, tracking down a number of constructions in which the clausal left-periphery is activated. First, we considered the appearance of the different complementizer particles in the CP-system, which overtly realize the three distinct functional projections ForceP, IntP and FinP, the backbone of the peripheral system. The analysis revealed that, already in the third year of life, children acquiring Italian correctly use these complementizer particles. Second, we looked for the simultaneous activation of different functional projections within the CP-System. We went through our corpus searching for complex sentences in which more than one constituent was moved to the left periphery. This option is allowed by the adult grammar of Italian and, as our search revealed, it is also attested in the grammar of young children. Soon after their second birthday, sequences in which a left-dislocated Topic and a Wh- element co-occur are attested, directly supporting the existence of a (high) Topic position above FocusP. Moreover, movement in general conforms to the constraints of the adult grammar, with no attested violation of obligatory inversion (a consequence of the Q-Criterion). Importantly, "why-questions" did not require inversion, much as in the adult grammar of Italian. Taken together, children's use of complementizer particles and their activation of multiple landing sites for movement show that 2-year-olds already possess a richly articulated functional structure of the CP-System, aligned to the layered adult structure uncovered in cartographic studies (Rizzi & Bocci 2017, Rizzi & Cinque 2016). In concluding the paper, we also discuss some temporal differences between constructions activating high and low portions of the CP-System. In particular, we detect a temporal precedence for wh-questions over why-questions. Since the former activate a lower projection, this is consistent with the recently proposed Growing Trees hypothesis (Friedmann, Belletti & Rizzi 2020), according to which the development of the CP-system proceeds stepwise.